Greco-Roman and Jewish tributaries to the New Testament festschrift in honor of Gregory J. Riley - Crawford, Christopher S.; Riley, Gregory J. 1947- (Claremont, CA Claremont Press, 2019)
"This volume explores the Greco-Roman and Jewish origins of the New Testament and early Christianity. It pays particular attention to the gospels and the traditions which place those sacred texts."--Publisher statement
Includes bibliographical references (pages 193 -209) and indexes
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Riley, Gregory J -- 1947-; Bible -- Criticism, interpretation, etc; Greek literature -- Relation to the New Testament; Intertextuality in the Bible; Bible; Greek literature ; Relation to the New Testament; Criticism, interpretation, etc; Festschrift; Aufsatzsammlung